Identifying Aesthetic Quality Attributes Using Kano Model: Case Study of Malay Women’s Office Outfit Design - Akmal, Suriati; Hambali, Ruzy Haryati; Tormudzi, Umi Nurnajeha; Kamalrudin, Massila; Hakimi, Halimatun (International Journal of Sustainable Construction Engineering and Technology, 2023)
The purpose of this study was to use the Kano model to prioritize the aesthetic quality attributes of modern Malay women’s office outfits that have significant effect on customer satisfaction using the Kano model. It is a systematic approach to categorize the customer requirements through a preference classification technique. Overall, 500 customers from the central part of Melaka have been surveyed using a Kano-based questionnaire. The questionnaire in the survey includes customer preferences on purchasing decision, material and design considerations, words that represent customer emotions toward aesthetic attributes and functional and dysfunctional aesthetic attributes. Based on responses, this study has categorized Malay women’s office outfits as attractive, must-be, one-dimensional, and reverse. Among the ten quality attributes that have satisfaction indices greater than 0.7, only one aesthetic quality attribute, free size, is defined as a one-dimension requirement. It should be offered in a Malay women’s office outfit to avoid customer dissatisfaction. The findings of this study facilitate cloth manufacturers to classify quality features during product design and development.